(untitled) (International Journal of Management and Sustainability, 2019)
This study looks at how increasing efficiency drives the production of the bioenergy in the European Union (EU-28) region. The paper used the Data Envelopment Analysis (DEA) statistical approach to use the cost efficiency (CE) rate of the bio-energy industry of the EU-28 region as a dependent variable of this study in the first stage of analysis. The study’s second stage analysis used the Tobit Model to investigate the impact of economic determinants on the CE of the bioenergy industry in the EU-28 region during the period between 1990 to 2013. The results of the second stage panel regression using Tobit model for the EU-28 region during 1990-2013 shows that CE has positive and significant correlations with capital cost (lnCI) and labour cost (lnLI). The results also show that cost efficiency and real interest rate (lnRIR).have a negative and significant relationship. The study showed that gross domestic product (lnGDP) and CE have a positive and significant relationship in the time specific model, but not in the country specific model. In addition, there is significant and positive correlations between CE and both the Interaction Dummy Country factor (Dum_CP) and the Country Dummy factor (Dum). The estimation also showed insignificant correlations between CE and both the Interaction Dummy Time factor (Dum_CP) and the Time Dummy factor (Dum).